The Role of English for Specific Purposes (ESP)-Based English Textbooks in Training Higher-Order Thinking Skills in Law Faculty Students - Marita, Yosi; Hidayat , Ade (Corolla International Conference, 2025)
The mastery of English for Specific Purposes (ESP) has become an essential need for Law Faculty students in facing the challenges of globalization and an increasingly competitive job market. This study aims to determine the role of ESP-based English textbooks in developing higher-order thinking skills in Law Faculty students. The research employed a qualitative method. Data were collected through interviews, questionnaires, and observations involving students and lecturers teaching ESP courses in several Law study programs. The results of the study show that the English for Specific Purposes (ESP)-based English textbooks used are effective in training students’ higher-order thinking skills during the learning process, strengthening their reading skills within the context of legal studies, and fostering critical and collaborative thinking abilities. The feasibility test indicates that the Legal English textbook received a “highly appropriate” rating from material and media experts, with an average score of 92%. The role of this Legal English textbook is considered effective in improving students’ English language competence in the Law Faculty. Therefore, the ESP-based English textbook used can serve as an innovative reference for English language learning at Prof. Dr. Hazairin, SH University.